The implementation of the monitoring and evaluation system in the office of the premier, Limpopo Province. - Mokgalaka, Shirley (My University, 2021)
Refer to the document
Thesis (MPA.) -- University of Limpopo, 2021
Keywords: Office of the premier in Limpopo Province; Monitoring; Evaluation; Government-wide Monitoring and Evaluation System; Evaluation; Job evaluation; Performance standards; Performance -- Evaluation